SPELLING BEE TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Sulviana Sulviana; Sitti Nurjannah; Nurul Ilmi Usfadila (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2023)
This study aims to investigate the effects of spelling bees on the ability to use the English language and their vocabulary. A non-equivalent control group design was employed in the Quasi-experimental study. Students enrolled in their seventh year at SMPN 9 Makassar make up the study's population. There were a total of 40 students; 20 were randomly assigned to the experimental group from VII C, and 20 were assigned to the control group from VII D. Students' vocabulary knowledge served as the dependent variable in this research, while spelling bees served as the independent variable. The research tool for this study was a vocabulary test that was administered before and after the intervention. A method known as purposive sampling was employed in this study. The research found that the experimental class had a pre-test spelling bee score of 53.60 and the control class had a score of 50.75. The experimental class had a post-test score of 75.65, while the control class achieved a score of 60.67. Researchers found that students' English vocabulary was significantly enhanced when they participated in spelling bees.